2022
DOI: 10.1186/s12883-022-02999-2
|View full text |Cite
|
Sign up to set email alerts
|

Double jeopardy - pituitary apoplexy complicated by ruptured aneurysm of the internal carotid artery within an adenoma: a case report

Abstract: Background Sudden onset of severe headache is the most common presentation of a ruptured intracranial aneurysm. Similar symptoms can be caused by pituitary apoplexy, and radiological examination is needed to distinguish between the two. Development of infarction and/or haemorrhage of the hypophysis with concomitant unruptured cerebral aneurysm has been described. However, intratumoural aneurysm within a pituitary adenoma presenting with the ictus of both pathologies is extremely rare. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…One of these cases showed that, at 6 months, complete functional recovery of the pituitary gland postoperatively was not achieved, though functional improvement via hormone loading test was confirmed ( 24 ). Other cases reported complete functional recovery at 3-month ( 18 ) and 10-month ( 23 ) follow-up visits, while one group of authors showed no improvement at 1 month after treatment ( 25 ); no further pituitary function assessments were reported for either of the cases. Another group of authors reported a case of a giant ICA aneurysm with pituitary dysfunction successfully treated with high-flow bypass using radial artery graft followed by ligation of the ICA at the cervical portion; at the 1-year follow-up, the patient presented with normal pituitary hormone levels, and at the 8-year follow-up visit, remained without hormonal replacement therapy, with good patency of the graft confirmed by MRI ( 26 ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…One of these cases showed that, at 6 months, complete functional recovery of the pituitary gland postoperatively was not achieved, though functional improvement via hormone loading test was confirmed ( 24 ). Other cases reported complete functional recovery at 3-month ( 18 ) and 10-month ( 23 ) follow-up visits, while one group of authors showed no improvement at 1 month after treatment ( 25 ); no further pituitary function assessments were reported for either of the cases. Another group of authors reported a case of a giant ICA aneurysm with pituitary dysfunction successfully treated with high-flow bypass using radial artery graft followed by ligation of the ICA at the cervical portion; at the 1-year follow-up, the patient presented with normal pituitary hormone levels, and at the 8-year follow-up visit, remained without hormonal replacement therapy, with good patency of the graft confirmed by MRI ( 26 ).…”
Section: Discussionmentioning
confidence: 97%
“…One of these cases showed that, at 6 months, complete functional recovery of the pituitary gland postoperatively was not achieved, though functional improvement via hormone loading test was confirmed (24). Other cases reported complete functional recovery at 3-month (18) and 10-month (23) follow-up visits, while one group…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation